Field study on non-invasive and non-destructive condition assessment for asbestos cement pipelines by time-domain fluid transient analysis. (January 2016) - Gong, Jinzhe; Lambert, Martin; Zecchin, Aaron; Simpson, Angus; Arbon, Nicole; Kim, Young-il
Asbestos cement pipelines constitute a significant portion of the potable and waste water systems in many countries in the world, including Australia. Most of the asbestos cement pipes in the developed countries were installed before 1980, and many utilities are observing that the breakage rate is increasing with the ageing of the pipe. Condition assessment for asbestos cement pipes is of important necessity for prioritising rehabilitation and preventing catastrophic pipe failure; however, few techniques are available for direct assessment of the condition of asbestos cement pipes and most of them are localised and destructive. This article outlines a pilot field study of the non-invasive and non-destructive condition assessment of asbestos cement pipelines using fluid transient pressure waves. Fluid transient analysis previously conducted by the authors for metallic pipelines is further developed and adapted to asbestos cement pipes for the detection of localised defects. A new sub-sectional condition assessment technique is proposed for determining the effective wall thicknesses of asbestos cement sub-sections within a section of pipe bounded by two measurement points. A field trial is conducted in Australia on an asbestos cement water main (which has class changes with varying wall thicknesses) to verify the proposed techniques. The wave speeds, lengths and wall thicknesses of sub-sections in different classes are determined and the results are consistent with the information in the design drawings provided by the water utility. This field study, for the first time, verifies that controlled fluid transient waves can be used as a tool for non-invasive and non-destructive condition assessment of asbestos cement pipelines.